Artificial General Intelligence and Panentheism - Li, Oliver (Theology and science, 2023)
In this article, I argue that given the possibility and prospect of Artificial General Intelligence (AGI), panentheism, as a form of theism with a stronger emphasis on the immanence of God, parallels the anti-anthropocentrism implied by AGI. I discuss some general issues related to the categorization of Artificial Intelligence (AI). Next, both anthropomorphism and anthropocentrism will be discussed as concepts for how humans may relate to AI. Subsequently, I argue and conclude that there is an analogy between the anti-anthropocentric implications of AGI and the anti-anthropocentric element of panentheism, but that panentheism points to a stronger form of anti-anthropocentrism.